Time changer - Christiano, Rich, 1956-; Downes, Kevin; Morin, D. David; MacLeod, Gavin, 1931-2021.; Linden, Hall.; Riehle, Richard, 1948-; O'Neill, Jennifer, 1948-; Rodriguez, Paul.; Hurn, Philip; Hollis, Jeffrey Lee.; Randall, Jasper; Five & Two Pictures (Firm); et al. ([S.l.] : Five & Two Pictures : TBN, 2002)
A philosopher and college professor is sent into the future to see the possible results of his actions in this mixture of sci-fi adventure and Christian drama.
DVD, Dolby surround, Dolby digital 5.1 surround.
English or Spanish dialogue; Closed-captioned.
D. David Morin, Gavin MacLeod, Hall Linden, Richard Riehle with Jennifer O'Neill and Paul Rodrigues as "Eddie."
Director of photography, Philip Hurn ; editor, Jeffrey Lee Hollis ; music, Jasper Randall.
"Original theatrical release"--Label.
MPAA rating: PG.
Keywords: College teachers -- Drama; Time travel -- Drama; Christian life -- Drama; Science fiction films; Fiction films; Feature films; Christian films; Video recordings for hard of hearing people